Designing Lesson Plan in Science Based on TPACK Framework - Sridevi, K. V. (SCHOOL SCIENCE, 2020)
Technological Pedagogical Content Knowledge (TPACK) has been introduced as a conceptual framework based on the notion that teachers need to align and integrate content, pedagogy, and technology in their teaching practice in order to make the classroom process interactive and learning meaningful and effective. This paper presents a brief description of how to design and develop a lesson plan based on the TPACK framework in teaching science with illustrations in a systematic manner.